2004
DOI: 10.1530/eje.0.1510447
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous administration of ghrelin stimulates growth hormone secretion in vagotomized patients as well as normal subjects

Abstract: Objective: Ghrelin is a potent peptide stimulating GH secretion. Besides its direct action on the pituitary, ghrelin has been reported to stimulate GH release via the vagal afferent nerve in rats. To examine the involvement of vagal nerve in ghrelin-induced GH secretion in humans, GH responses to ghrelin were compared between vagotomized patients with gastrectomy and normal subjects. Methods: Ghrelin (0.2 mg/kg) or GHRH (1 mg/kg) was administered intravenously in vagotomized patients and normal subjects on sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 23 publications
2
17
0
1
Order By: Relevance
“…11 Takeno et al have recently described a normal GH response to continuous intravenous ghrelin administration in vagotomised humans. 41 In support of this, in the current study, all subjects showed a significant GH secretory response to intravenous ghrelin with no correlation between CAN and GH levels.…”
Section: Discussionsupporting
confidence: 70%
“…11 Takeno et al have recently described a normal GH response to continuous intravenous ghrelin administration in vagotomised humans. 41 In support of this, in the current study, all subjects showed a significant GH secretory response to intravenous ghrelin with no correlation between CAN and GH levels.…”
Section: Discussionsupporting
confidence: 70%
“…1, D-F). In the high-dose treatment, the rats treated with either of the ghrelin agonists BIM-28125 and BIM-28131, as well as the rats treated with ghrelin, gained lean mass compared with the controls (42,49,46, and 29%, respectively, P Ͻ 0.001). However, the major weight gain in the high-dose groups was due to an increase in fat mass (BIM-28125, 234%; BIM-28131, 298%; ghrelin, 248%; and vehicle, 52%).…”
Section: Resultsmentioning
confidence: 97%
“…Hypothalamic neurons producing these two neuropeptides also express the GHS-R (19,55). Despite controversial reports based on models (3,10), afferent signaling of the vagus nerve does not seem to play an important role for metabolic actions of ghrelin, as shown in humans (49). Although there are numerous peptides affecting appetite or eating behavior in rodents, ghrelin is the first and only gut peptide with orexigenic properties in humans (7,38).…”
mentioning
confidence: 99%
“…Critically, it points to the fact that vagal signalling is not essential to relay ascending orexigenic messages, likely due to the fact that the area postrema can facilitate diffusive access of ghrelin from the bloodstream to the NTS, enabling ascending signalling even without vagal innervation of the NTS. This is supported by the fact that intravenous ghrelin administration stimulates growth hormone secretion in vagotomised patients [208]. Taken together, all of the above information strongly suggests an interlinked role between blood and neural pathways for conveying ghrelin’s signal from the periphery to the CNS.…”
Section: Ghrelin and Ghrelin Ligands: Pharmacokinetic Perspectivesmentioning
confidence: 90%